REHABILITATION OF DEVASTATED PEAT LANDS AND ESTABLISHMENT OF SUSTAINABLE AGRO-SYSTEMS THROUGH BUFFER ZONE PLANNING IN CENTRAL KALIMANTAN - Mitsuru Osaki; Hanny Wijaya; Herwint Simbolon (Research Center for Biology-Indonesian Institute of Sciences, 2000)
-